Porcine circovirus type 2 affects the serum profile of amino acids and intestinal expression of amino acid transporters in mice. Issue 90 (1st October 2015) - Xiao, Dingfu; Yin, Jie; Ren, Wenkai; He, Jianhua; Hu, Xionggui; Yin, Yulong; Luo, Wei; Yu, Xinglong
<x xml:space="preserve">Abstract</x> PCV2 is highly pathogenic, however, its effect on the serum amino acids profile is unknown.